Percutaneous versus open pedicle screw fixation for treatment of type A thoracolumbar fractures - Kocis, Jan; Kelbl, Martin; Kocis, Tomas; Návrat, Tomas (European journal of trauma and emergency surgery, 2020)
BACKGROUND: The purpose of this study was to evaluate the effectiveness between percutaneous and open pedicle screw fixation without fusion for treating type A3 and A4 thoracolumbar fractures. Traumatic thoracolumbar burst fracture is a common pathology without a consensus on the best treatment approach. Percutaneous pedicle screw fixation (PPSF) systems have been recently introduced in the treatment of spinal fractures to reduce the adverse effects associated with the conventional open approaches, such as iatrogenic muscle denervation and pain. METHODS: A prospective analysis was made to evaluate consecutive 46 patients with type A3 and A4 thoracolumbar fractures. Patients were divided into a percutaneous pedicle screw fixation group (PPSF) and an open pedicle screw fixation group (OPSF). The mean age of patients in PPSF group (12 men, 11 woman) was 49.9 years and in OPSF group (10 men, 13 women) 52.2 years. For the purpose of evaluation, the radiological assessment of the bisegmental Cobb angle, the loss of correction, the volume of blood loss, operation time, cumulative radiation time and dose were recorded and compared. RESULTS: All patients were followed up for 12 months. There were no significant differences between OPSF and PPSF in the Cobb angle preoperative and postoperative angle and the loss of bisegmental correction. In PPSF group, the mean preoperative Cobb angle was 10.9° and improved by 4.5° postoperatively, and in OPSF group the preoperative angle was 12.1° and postoperatively improved by 3.8°. Significant differences between OPSF and PPSF were found in the mean cumulative radiation time, radiation dose and operation time. PPSF group also had a significantly lower perioperative blood loss. CONCLUSIONS: Both open and percutaneous short-segment pedicle fixation were safe and effective methods to treat thoracolumbar burst fractures. Percutaneous fixation without fusion seems to be suitable for type A3 and A4 fractures.
Keywords: fraktury páteře; dospělí; krvácení při operaci; Female; Operative Time; Adult; výsledek terapie; mladý dospělý; ženské pohlaví; Blood Loss, Surgical; lidé; pedikulární šrouby; bederní obratle; Thoracic Vertebrae; Treatment Outcome; Pedicle Screws; Minimally Invasive Surgical Procedures; kohortové studie; Cohort Studies; prospektivní studie; Male; Aged; Lumbar Vertebrae; Prospective Studies; Young Adult; hrudní obratle; délka operace; vnitřní fixace fraktury; lidé středního věku; Spinal Fractures; senioři; mužské pohlaví; Radiation Dosage; miniinvazivní chirurgické výkony; dávka záření; Middle Aged; Fracture Fixation, Internal; Humans